THE IMPACT OF RAMADAN ON ECONOMIC GROWTH AND CHANGES IN THE CONSUMPTION PATTERNS OF MUSLIM COMMUNITIES IN SURABAYA THROUGH THE BUKBER CULTURE - Syamsul Ma’arif; Ahmad Fathoni (el Hakim Press, 2025)
Ramadhan is a significant moment in the lives of Muslims, bearing not only spiritual meaning but also notable social and economic impacts. One of the distinctive traditions that emerges during Ramadhan is the culture of communal fast-breaking, known as Bukber, which strengthens social interaction while simultaneously driving economic activity, particularly in the culinary and retail sectors. This study aims to analyze the influence of Ramadhan on economic growth and shifts in consumption patterns among the Muslim community in Surabaya, with Bukber culture serving as a mediating variable. This research employs a mixed-method approach, combining quantitative and qualitative methods. Data collection was conducted through surveys involving 100 respondents using a Likert-scale questionnaire, in-depth interviews, and direct observation. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) via the SmartPLS 4.0 software. The findings indicate that Ramadhan significantly affects economic growth (? = 0.42, t = 5.25) and changes in consumption patterns (? = 0.55, t = 7.86). The Bukber tradition also significantly influences both economic growth (? = 0.37, t = 4.11) and consumption patterns (? = 0.48, t = 8.00), while also partially mediating the effect of Ramadhan on both endogenous variables. The coefficient of determination (R²) shows that consumption patterns are strongly influenced by Ramadhan and Bukber (R² = 0.63), while economic growth falls within the moderate-to-strong category (R² = 0.58). The mediation effects along the paths Ramadhan ? Bukber ? Economic Growth (? = 0.23) and Ramadhan ? Bukber ? Consumption Patterns (? = 0.30) are also statistically significant. The study concludes that Ramadhan and the Bukber tradition contribute significantly to the socio-economic dynamics of urban communities. Bukber not only reinforces social solidarity but also serves as a driver of local economic development. Therefore, strategic management of this tradition can be integrated into sustainable, community-based economic development policies.